2021
DOI: 10.1097/mco.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the gut microbiome in gluten-intolerance

Abstract: Purpose of review Gluten is a complex mixture of highly immunogenic glutamine- and proline-rich proteins found in some cereals. In celiac disease (CeD), gluten triggers an autoimmune response due to its interaction with the human leukocyte antigen heterodimers that confer the genetic risk. The involvement of gluten in other disorders has also been investigated, but its role beyond CeD is still unclear. Here, we review the most recent evidence of the involvement of gluten in diseases and the opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…To understand the role of some bacterial clusters in the modulation of the immune response, De Palma et al [22] evaluated the effects of Bifidobacterium bifidum and Bifidobacterium longum alone or with celiac disease triggers on peripheral-blood mononuclear cells, comparing these effects with those of Gram-negative bacteria such as E. coli and Bacteroides fragilis. In this study, it was noted that Gram-negative bacteria induced a greater Th-1 secretion response to proinflammatory cytokines and the activation of other mechanisms such as IFN-c, IL-12, HLA-DR, and CD40 compared with Bifidobacteria species [21]. On the other hand, the latter increased the expression of CD83, which is a marker of mature dendritic cells.…”
Section: Role Of Probiotics and Regulation Of The Immune Responsementioning
confidence: 72%
See 2 more Smart Citations
“…To understand the role of some bacterial clusters in the modulation of the immune response, De Palma et al [22] evaluated the effects of Bifidobacterium bifidum and Bifidobacterium longum alone or with celiac disease triggers on peripheral-blood mononuclear cells, comparing these effects with those of Gram-negative bacteria such as E. coli and Bacteroides fragilis. In this study, it was noted that Gram-negative bacteria induced a greater Th-1 secretion response to proinflammatory cytokines and the activation of other mechanisms such as IFN-c, IL-12, HLA-DR, and CD40 compared with Bifidobacteria species [21]. On the other hand, the latter increased the expression of CD83, which is a marker of mature dendritic cells.…”
Section: Role Of Probiotics and Regulation Of The Immune Responsementioning
confidence: 72%
“…Studies on infants [20] have shown that infants with a high genetic risk of CD have gut microbiota comprising higher proportions of Proteobacteria and Firmicutes and lower proportions of Bifidobacteria and Actinobacteria. Other studies [21,22] have reported that milk feeding plus the HLA-DQ genotype has an impact on infant gut microbiota compositions. Gut bacteria such as the Lactobacilli and Bifidobacterium strains may have some advantages in patients with a high risk of CD.…”
Section: The Role Of Gut Microbiota and Its Modulation With Probiotic...mentioning
confidence: 98%
See 1 more Smart Citation
“…Исследования на младенцах [20] показали, что дети с высоким генетическим риском Ц имеют кишечную микробиоту, представленную преимущественно протеобактериями и фирмикутами и в меньшей степени бифидо-и актинобактериями. В других исследованиях [21,22] сообщается, что вскармливание формулами на основе коровьего молока младенцев с генотипом HLA-DQ -фактора риска развития 125 À Архив педиатрии и детской хирургии № 1 [2] 2024 года Ц, оказывает влияние на состав микробиоты кишечника. Кишечные бактерии, такие как штаммы Lactobacilli и Bifi dobacterium, могут иметь некоторые преимущества у пациентов с высоким риском Ц, поскольку они могут модулировать иммунный ответ на глютен и его пептиды.…”
Section: роль микробиоты кишечника и ее коррекция пробиотиками при це...unclassified
“…Исследования на младенцах [20] показали, что дети с высоким генетическим риском Ц имеют кишечную микробиоту, представленную преимущественно протеобактериями и фирмикутами и, в меньшей степени, бифидо-и актинобактериями. В других исследованиях [21,22] сообщается, что вскармливание формулами на основе коровьего молока младенцев с генотипом HLA-DQ -фактора риска развития Ц, Гастроэнтерология оказывает влияние на состав микробиоты кишечника. Кишечные бактерии, такие как штаммы Lactobacilli и Bifi dobacterium, могут иметь некоторые преимущества у пациентов с высоким риском Ц, поскольку они могут модулировать иммунный ответ на глютен и его пептиды.…”
Section: роль микробиоты кишечника и ее коррекция пробиотиками при це...unclassified